Senegal's Infrastructure : A Continental Perspective - Torres, Clemencia; Briceno-Garmendia, Cecilia M.; Dominguez, Carolina (2012)
Infrastructure contributed 1 percentage point to Senegal's improved per capita growth performance between 2000 and 2005, placing it in the middle of the distribution among West African countries. Raising the country's infrastructure endowment to that of the region's middle-income countries (MICs) could boost annual growth by about 2.7 percentage points. Senegal has made significant progress in some areas of its infrastructure, including the transport, electricity, water, and information-and-communication-technology (ICT) sectors. But looking ahead, the country faces important infrastructure challenges, including improving road conditions, boosting air and rail traffic, updating electricity infrastructure, and boosting the pace of expansion of the water-and-sanitation network. Senegal currently spends around $911 million per year on infrastructure, with $312 million lost annually to inefficiencies. Comparing spending needs with existing spending and potential efficiency gains leaves an annual funding gap of $578 million per year. Senegal has the potential close this gap by bringing in more private-sector investment.